Analysis of Differences in Critical Thinking Skills in Relation to Students’ Mathematical Resilience in SPLDV Curriculum - Nurul Nurhayati; Musthofiatur Rochmah; Sintha Sih Dewanti; Zupia Annisa (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2026)
Critical thinking skills are an important yet difficult competency to develop in mathematics learning at the junior high school level. This study aims to analyze differences in students’ critical thinking skills in terms of three categories of mathematical resilience: high, moderate, and low. The research design used in this study is quantitative research with a comparative approach. The sample was selected using cluster sampling, consisting of 29 eighth-grade students from Class VIII C at a junior high school in Yogyakarta. Data collection techniques included a questionnaire and a test. The questionnaire comprised 20 Likert-scale statements (1-4) to measure mathematical resilience, while the test consisted of 5 items to assess critical thinking skills, specifically regarding the topic of Systems of Linear Equations with Two Variables. The analysis technique used was parametric analysis employing a One-Way ANOVA test. The results indicated no significant difference in critical thinking ability between categories of mathematical resilience, with an F- value of 2.572 and a significance level of 0.096 (p > 0.05). This finding indicates that the two constructs operate relatively independently; therefore, the development of critical thinking skills requires learning strategies that directly train analytical and evaluative abilities.